ANALISIS STRATEGI PENGELOLAAN PARIWISATA DI MASA COVID-19 (STUDI DI WISATA PANTAI LOVINA KABUPATEN BULELENG) - Nyoman Dane; Ni Putu Rika Sukmadewi (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
AbstractThe Covid-19 outbreak has hit a number of sectors of life. This epidemic not only threatens the health of the citizens, but also the joints of economic life, and one of them is the tourism sector. One of the tours that have felt the impact of the Covid-19 pandemic in Indonesia is located in Buleleng Regency, Bali, namely Lovina Beach which is an icon of North Bali Tourism in Buleleng Regency which has its own charm in attracting tourists. The essence to be conveyed is how the process of tourism management in Buleleng Regency during this pandemic. This study uses a qualitative research type with a descriptive approach. The strategy for managing Lovina beach tourism during the Covid-19 period is good, because during this Covid-19 period, Lovina beach tourism managers are able to take advantage of technological sophistication, namely by marketing tourism products through online media. Supporting factors in the management of Lovina Beach tourism during the Covid-19 pandemic, namely: (1) granting permits from the Buleleng Regency Government; (2) cooperation of Lovina Beach with the Government of Buleleng Regency; (3) direct supervision from the Buleleng Regency Covid group team towards every tourist. While the inhibiting factors in managing Lovina Beach tourism during the Covid pandemic, among others: (1) lack of manpower; (2) visitors who do not comply with health protocols; (3) the public does not know if Lovina Beach tourism has been reopened; and (4) management income decreased. Keywords: Strategy, management, tourism